Exploring flow occurrence in elite golf - Swann, C.; Keegan, R.; Pigott, D.; Crust, L.; Smith, M. F. (2011)
Research on flow (Csikszentmihalyi, 1975) has traditionally focused on reactive, externally-paced sports (e.g., tennis) without exploring those that are self-paced and stop-start in nature. This study investigated the occurrence of flow in a sample of thirteen elite golfers by conducting semi-structured interviews discussing: (i) their experiences of flow, (ii) factors that influenced flow occurrence, and (iii) the controllability of these experiences. Results shared similarity with existing research in terms of the majority of influencing factors reported, including motivation, preparation, focus, psychological state, environmental and situational conditions, and arousal, and that flow was reported to be at least potentially controllable. Golf-specific influences were also noted, including pre-shot routines, use of psychological interventions, standard of performance, and maintenance of physical state, suggesting that flow may have occurred differently for this sample. Findings are discussed and applied recommendations are made that may help golfers put relevant factors in place to increase the likelihood of experiencing flow.